Labor Pooling in R&D Intensive Industries - Heiko A. Gerlach; Thomas Rønde; Konrad O. Stahl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
We investigate the interplay between firms' R&D decisions and labor market competition, and how this influences equilibrium location choices and welfare. Firms engage in risky R&D activities and thus create stochastic product and implied labor demand. Spatial agglomeration is more likely in situations where the innovation step is large and the probability for a firm to be the only innovator is high. When firms agglomerate, they tend to invest more in R&D compared to spatially dispersed firms. Agglomeration is welfare maximizing, because expected labor productivity is higher and firms choose a more efficient, diversified portfolio of R&D projects at the industry level. The latter aspect is ascertained by data from German firms in R&D intensive industries.
Keywords: R12; O32; L13; 330; Facharbeiter; Betriebliche Forschung; Betriebliche Standortwahl; Regionale Konzentration; Forschung; Schätzung; Theorie; Deutschland